Let \( A=\left[\begin{array}{cc}-5 & 0 \\ 0 & 4\end{array}\right] \) and \( B=\left[\begin{array}{cc}-2 & 0 \\ 0 & 1\end{array}\right] \). Find each matrix below. If a matrix is not defined, click on "Undefined". (a) \( B A= \) \( \square \) (b) \( A B= \) \( \square \) (c) \( B^{2}- \) \( \square \) Check
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Mind Expander
To calculate \(B A\) and \(A B\), we will perform matrix multiplication. (a) \(B A = \left[\begin{array}{cc}-2 & 0 \\ 0 & 1\end{array}\right] \left[\begin{array}{cc}-5 & 0 \\ 0 & 4\end{array}\right] = \left[\begin{array}{cc}(-2)(-5) + (0)(0) & (-2)(0) + (0)(4) \\ (0)(-5) + (1)(0) & (0)(0) + (1)(4)\end{array}\right] = \left[\begin{array}{cc}10 & 0 \\ 0 & 4\end{array}\right]\) (b) \(A B = \left[\begin{array}{cc}-5 & 0 \\ 0 & 4\end{array}\right] \left[\begin{array}{cc}-2 & 0 \\ 0 & 1\end{array}\right] = \left[\begin{array}{cc}(-5)(-2) + (0)(0) & (-5)(0) + (0)(1) \\ (0)(-2) + (4)(0) & (0)(0) + (4)(1)\end{array}\right] = \left[\begin{array}{cc}10 & 0 \\ 0 & 4\end{array}\right]\) (c) \(B^{2} = B \times B = \left[\begin{array}{cc}-2 & 0 \\ 0 & 1\end{array}\right] \left[\begin{array}{cc}-2 & 0 \\ 0 & 1\end{array}\right] = \left[\begin{array}{cc}4 & 0 \\ 0 & 1\end{array}\right]\) So the results are: (a) \( B A = \left[\begin{array}{cc}10 & 0 \\ 0 & 4\end{array}\right] \) (b) \( A B = \left[\begin{array}{cc}10 & 0 \\ 0 & 4\end{array}\right] \) (c) \( B^{2} = \left[\begin{array}{cc}4 & 0 \\ 0 & 1\end{array}\right] \)